Acute skeletal muscle wasting and dysfunction predict physical disability at hospital discharge in patients with critical illness - Mayer, Kirby P. (Crit Care, 2020)
BACKGROUND: Patients surviving critical illness develop muscle weakness and impairments in physical function; however, the relationship between early skeletal muscle alterations and physical function at hospital discharge remains unclear. The primary purpose of this study was to determine whether changes in muscle size, strength and power assessed in the intensive care unit (ICU) predict physical function at hospital discharge. METHODS: Study design is a single-center, prospective, observational study in patients admitted to the medicine or cardiothoracic ICU with diagnosis of sepsis or acute respiratory failure. Rectus femoris (RF) and tibialis anterior (TA) muscle ultrasound images were obtained day one of ICU admission, repeated serially and assessed for muscle cross-sectional area (CSA), layer thickness (mT) and echointensity (EI). Muscle strength, as measured by Medical Research Council-sum score, and muscle power (lower-extremity leg press) were assessed prior to ICU discharge. Physical function was assessed with performance on 5-times sit-to-stand (5STS) at hospital discharge. RESULTS: Forty-one patients with median age of 61 years (IQR 55–68), 56% male and sequential organ failure assessment score of 8.1 ± 4.8 were enrolled. RF muscle CSA decreased significantly a median percent change of 18.5% from day 1 to 7 (F = 26.6, p = 0.0253). RF EI increased at a mean percent change of 10.5 ± 21% in the first 7 days (F = 3.28, p = 0.081). At hospital discharge 25.7% of patients (9/35) met criteria for ICU-acquired weakness. Change in RF EI in first 7 days of ICU admission and muscle power measured prior to ICU were strong predictors of ICU-AW at hospital discharge (AUC = 0.912). Muscle power at ICU discharge, age and ICU length of stay were predictive of performance on 5STS at hospital discharge. CONCLUSION: ICU-assessed muscle alterations, specifically RF EI and muscle power, are predictors of diagnosis of ICU-AW and physical function assessed by 5x-STS at hospital discharge in patients surviving critical illness.